Learning, teaching, and musical identity : voices across cultures - Green, Lucy (Counterpoints (Bloomington, Ind.), 2011)
Musical identity raises complex, multifarious, and fascinating questions. Discussions in this new study consider how individuals construct their musical identities in relation to their experiences of formal and informal music teaching and learning. Each chapter features a different case study situated in a specific national or local socio-musical context, spanning 20 regions across the world. Subjects range from Ghanaian or Balinese villagers, festival-goers in Lapland, and children in a South African township to North American and British students, adults and children in a Cretan brass band, and Gujerati barbers in the Indian diaspora.